2012
DOI: 10.1021/jf303177p
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Action of Photoirradiated Gallic Acid via Reactive Oxygen Species Formation

Abstract: It is known that gallic acid shows antimicrobial activity. In the present study, photoirradiation induced reactive oxygen species formation was investigated for augmentation of the antimicrobial activity of gallic acid. Staphylococcus aureus suspended in 4 mmol/L gallic acid was exposed to blue light of a LED at 400 nm. This treatment killed the bacteria, and a >5-log reduction of the viable counts was observed within 15 min. By contrast, neither the LED treatment alone nor the treatment with gallic acid alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 38 publications
5
89
0
Order By: Relevance
“…9−13 In our previous study, it was demonstrated that the antimicrobial activity of polyphenols, such as gallic acid and proanthocyanidin, was considerably enhanced by blue light irradiation at a wavelength of around 400 nm. 14,15 When Staphylococcus aureus suspended in an aqueous solution of the polyphenols was exposed to blue light, they were killed with a >5 log reduction of viable counts within 15−30 min.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9−13 In our previous study, it was demonstrated that the antimicrobial activity of polyphenols, such as gallic acid and proanthocyanidin, was considerably enhanced by blue light irradiation at a wavelength of around 400 nm. 14,15 When Staphylococcus aureus suspended in an aqueous solution of the polyphenols was exposed to blue light, they were killed with a >5 log reduction of viable counts within 15−30 min.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 Hydrogen peroxide (H 2 O 2 ) is produced via electron transfer from photo-oxidized polyphenols to dissolved oxygen. The H 2 O 2 is subsequently photolyzed by the blue light, resulting in the generation of hydroxyl radicals ( • OH), 16 which would be a main contributor of the bactericidal activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17.2). Nakamura et al demonstrated that hydroxyl radicals were generated when gallic acid, a polyphenolic compound, was irradiated with blue light (wavelength: 400 nm) at an irradiance of 80 mW/cm 2 [72]. It was also demonstrated that S. aureus was killed by the photo-irradiation of gallic acid with a >5-log reduction of viable counts within 15 min.…”
Section: Other Hydroxyl Radical Generation Systemsmentioning
confidence: 99%
“…It was reported that an important anticancer mechanism of plant polyphenols is mediated through intracellular copper mobilization and reactive oxygen species (ROS) generation, which is a characteristic feature of pro-oxidant properties of polyphenolic compounds, leading to cancer cell death (Khan et al 2014). In our previous studies, the pro-oxidant potential of polyphenols was applied to the development of a novel disinfection technique (Nakamura et al 2012b(Nakamura et al , 2013(Nakamura et al , 2015. Exposing an aqueous solution of polyphenols to blue light led to photooxidation of the polyphenolic hydroxyl group, resulting in the generation of hydrogen peroxide (H 2 O 2 ) produced via electron transfer from photooxidized polyphenols to dissolved oxygen.…”
Section: Introductionmentioning
confidence: 99%